Impact of Previous Local Treatment for Brain Metastases on Response to Molecular Targeted Therapy in BRAF-Mutant Melanoma Brain Metastasis: A Systematic Review and Meta-Analysis - Liao, Guixiang; Fu, Yuxiang; Arooj, Sumbal; Khan, Muhammad; Li, Xianming; Yan, Maosheng; Li, Zihuang; Yang, Hongli; Zheng, Tao; Xu, Ruilian (Frontiers in Oncology, 2022)
Background Melanoma brain metastases are associated with poor prognosis and are the main cause of mortality in melanoma patients. BRAF inhibitors have shown intracranial activity in both treatment-naïve and previously treated brain metastases (BMs) patients. We aimed to investigate if there was any difference in response of BRAF inhibitors in these two cohorts. Materials and Methods Electronic databases searched included PubMed, Medline, and Cochrane library until March 2021 for studies with desired comparative outcomes. Outcomes of interest that were obtained for meta-analysis included intracranial response rate as the primary, outcome and survival and safety outcomes as the secondary outcome. Review Manager version 5.4 was used for data analysis. Results Three studies comprising 410 BRAF-mutated melanoma patients with brain metastases (BMs) were included according to eligibility criteria. The comparative cohort included patients with treatment-naïve BMs (TN cohort; n=255) and those who had progressive disease after receiving local brain treatment for BMs (PT cohort; n=155). Meta-analysis revealed that BRAF inhibitors (vemurafenib and dabrafenib) and BRAF/MEK inhibitor combination (dabrafenib and trametinib) induced significantly higher intracranial disease control (OR 0.58 [95% CI; 0.34, 0.97], p=0.04) and a trend toward improved progression-free survival (PFS) (HR 1.22 (95% CI; [0.98, 1.52], p=0.08) in the PT cohort as compared to the TN cohort. Overall survival was not significantly different between the cohorts (HR 1.16 (95% CI; [0.89, 1.51], p=0.28). Subgroup analysis revealed that PFS was significantly improved (HR 1.67 [95% CI; 1.06, 2.62], p=0.03) and a trend toward improved OS (HR 1.62 [95% CI; 0.95, 2.75], p=0.08) was achieved in patients receiving BRAF/MEK inhibitor combination and patients with BRAFv600K mutation receiving dabrafenib alone. No increase in overall adverse events (AEs), grade 3/4 AEs, and severe adverse events (SAEs) was observed between the cohorts. Conclusions BRAF inhibitors (plus MEK inhibitor) may achieve better intracranial disease stability in BRAF-mutant melanoma patients who have received previous local treatment for brain metastases.